El patio iluminado, by Manuel Mujica Láinez. Modelling of an Integrated Discourse Analysis - González, Daniela Soledad (Revista Electrónica Educare, 2016)
For a complete understanding of a text, it must be addressed in an integrated way, linking the various levels of analysis and using various linguistic disciplines to explain it. In this paper, the text El patio iluminado, by Manuel Mujica Lainez, is analyzed considering the following aspects: graphic superstructure, semantic superstructure, pragmatic macrostructure, microstructure, propositional level, register, speech acts, explicatures, implicatures, rhetorical procedures, politeness strategies and polyphony. The aim of this paper is to provide an integrated textual analysis model to teachers –especially to those of superior level– to be used when explaining issues related to Pragmatics and Discourse Analysis.